Study on radionuclides uptake and radiation risk in selected vegetables grown in highlands area of Peninsular Malaysia / Marlinda Musa - Musa, Marlinda (2016)
The naturally occurring radionuclides which are ⁴⁰K, ²²⁶Ra and ²²⁸Ra are naturally present in the environment. However, the anthropogenic activity may cause their content to accumulate in the environment. Due to this, the hyper-accumulation of radionuclides such as ²²⁶Ra and ²²⁸Ra may cause a toxic especially once it have ingested by human through the contaminated foods such as vegetables. Cabbage, watercress and tomatoes were selected to represent the vegetables in this study. Objectives of this study are to determine the level of natural radionuclides in selected vegetables, soil/growing medium, water and non-organic and organic fertilizers and to estimate the uptake of radionuclides by selected vegetables. Finally the radiological risk analysis will be carried out of these vegetables. This study was conducted in two farmlands in Cameron Highlands, Pahang and one in Lojing, Kelantan. Samples were dried, ground and sieved prior to analysis. Analyses by of radioactivity concentration of radionuclides were done by using Gamma Spectrometer with high resolution hyper pure germanium (HPGe) detector. It has been analyzed after 2 weeks of sample preparation to achieve the equilibrium. For radionuclides concentration (U and preparation to achieve the equilibrium. For radionuclides concentration (U and Th), the analysis was done by using X-rays Fluorescence Spectroscopy (XRF)...